English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

6x - 5y = 12 and x + y 3

Multiply the first equation by 5 and the second by 6
Multiply the first equation by 6 and the second by 5.
Multiply the first equation by 5.
Multiply the second equation by -6

2006-12-23 12:49:01 · 9 answers · asked by Little Britches 3 in Science & Mathematics Mathematics

9 answers

Multiply the second equation by -6

You want one variable to be canceled out so that you can solve for the other.

2006-12-23 12:52:54 · answer #1 · answered by Mike J 3 · 3 0

the first step is to multiply between the equation with the help of a element which will make the coefficient of both x or y the same. And it does not count number which one is picked; the outcomes will be the same. in many circumstances, I %. the multiplication element which will bring about an person-friendly calculation. thus, that is less difficult to dissimilar the 2d equation with the help of - or +5. so that you get: -6x -6y = -18 [this facilitates you to remove the x's] or: 5x +5y = +15 [this facilitates you to remove the y's]

2016-12-01 03:15:01 · answer #2 · answered by ? 4 · 0 0

You would definately want to multiply the second equation by (-6) because then that "x" would become (-6x). On the other equation you have a positive (6x). Those two variables will cancel each othe rout and you will be left to solve for "y".

Voila

2006-12-23 13:03:14 · answer #3 · answered by Brian 1 · 2 0

Multiply the second equation by -6:
6x-5y=12
-6x-6y=-18
========
-11y=-6
y=6/11

x+6/11=3
x=33/11-6/11
x=27/11
(27/11,6/11)

Check:
6(27/11)-5(6/11)=12
162/11-30/11=12
132/11=12
12=12

27/11+6/11=3
33/11=3
3=3

2006-12-23 13:00:03 · answer #4 · answered by Anonymous · 3 0

The goal of the addition or elimination method is to eliminate one variable. Therefore the answer is the 4th one: multiplying the second equation by -6.

2006-12-23 12:51:53 · answer #5 · answered by Anonymous · 3 0

6x - 5y = 12
x + y = 3

(6x - 5y) + (x + y) = 12 + 3
6x - 5y + x + y = 15
7x - 4y = 15
-4y = -7x + 15
y = (7/4)x - (15/4)

x + ((7/4)x - (15/4)) = 3
x + (7/4)x - (15/4) = 3
4x + 7x - 15 = 12
11x - 15 = 12
11x = 27
x = (27/11)

(27/11) + y = 3
27 + 11y = 33
11y = 6
y = (6/11)

ANS : x = (27/11) and y = (6/11)

2006-12-23 13:32:42 · answer #6 · answered by Sherman81 6 · 0 0

6x - 5y = 12
x + y= 3 multiply by 5
5x+5y=15
6x - 5y = 12 add
11x=27
x=27/11
27/11+y=3
y=33/11-27/11=6/11

(27/11, 6/11)

2006-12-23 12:54:43 · answer #7 · answered by mu_do_in 3 · 3 0

It's a trick question. The second expression given (x+y 3) that we are suggested to take as an equation is not actually an equation, because it has no = mark.

There is only one equation and one non-equation, therefore there is no system of equations.

I suggest reposting the question.

2006-12-23 12:54:58 · answer #8 · answered by Piguy 4 · 3 0

1(6x - 5y = 12)
5(1x + y = 3)
------------------
6x - 5y = 12
+ 5x + 5y = 3
-----------------
11x = 15
11x/11 = 15/11
x = 15/11

-1(6x - 5y = 12)
6(1x + y = 3)
--------------------
-6x + 5y = -72
+ 6x + 6y = 18
---------------------
11y = -54
11y/11 = -54/11
y = - 54/11

2006-12-23 17:06:02 · answer #9 · answered by ♪♥Annie♥♪ 6 · 0 0

fedest.com, questions and answers